PKM Kewirausahaan “KEBAB PICUUY” Bagi Ibu Rumah Tangga di Kecamatan Manggala - Mustari Mustari; Nur Arisah; Nurjannah Nurjannah; Ratnah S; Sitti Hajerah Hasyim (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One of the activities that can increase the entrepreneurial spirit for the community is through a home industry business or commonly called a home business in making